2021
DOI: 10.1080/02699931.2021.2022602
|View full text |Cite
|
Sign up to set email alerts
|

Psychological trauma and emotional upheaval as revealed in academic writing: The case of COVID-19

Abstract: The current paper used a preregistered set of language dimensions to indicate how scientists psychologically managed the COVID-19 pandemic and its effects. Study 1 evaluated over 1.8 million preprints from arXiv.org and assessed how papers written during the COVID-19 pandemic reflected patterns of psychological trauma and emotional upheaval compared to those written before the pandemic. The data suggest papers written during the pandemic contained more affect and more cognitive processing terms to indicate wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 63 publications
7
22
0
Order By: Relevance
“…That is, the degree to which various measures of complexity can identify petitions that receive high or low numbers of supporters, or those that are victorious from those that fail, should be examined in future research with more sophisticated natural language processing techniques. Third, the effect sizes in the current paper are small, but consistent with those reported in other research (Kern et al, 2014;Kramer et al, 2014;Markowitz, 2022;Seraj et al, 2021). Many cases were required to identify such relationships.…”
Section: Limitations and Future Directionssupporting
confidence: 85%
See 2 more Smart Citations
“…That is, the degree to which various measures of complexity can identify petitions that receive high or low numbers of supporters, or those that are victorious from those that fail, should be examined in future research with more sophisticated natural language processing techniques. Third, the effect sizes in the current paper are small, but consistent with those reported in other research (Kern et al, 2014;Kramer et al, 2014;Markowitz, 2022;Seraj et al, 2021). Many cases were required to identify such relationships.…”
Section: Limitations and Future Directionssupporting
confidence: 85%
“…Two exploratory language dimensions related to other forms of complexity were evaluated as well: analytic thinking and readability. Analytic thinking is a proxy for Kahneman's (2011) System 2 thinking (Markowitz, 2022;Seraj et al, 2021), and is calculated as a composite variable of seven function word categories in LIWC (Pennebaker et al, 2014). 7 High scores indicate writers with a formal, concrete, and complex thinking style compared to low scores, which indicate writers with a narrative, dynamic, and simple thinking style.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cognitive processing words suggest that people try to make meaning from their traumatic experiences and re-organize their thoughts into a more coherent and less emotionally disturbing narrative ( Pennebaker & Harber, 1993 ). For instance, Markowitz (2022 , Study 1) found that scientists used more cognitive processing words in writings during the COVID-19 pandemic than before, revealing the academics’ attempts to construct meaning about heightened psychological distress.…”
Section: Psychological Adjustment and Language Usementioning
confidence: 99%
“…It is difficult to study how cognitive reappraisal unfolds as people are experiencing a traumatic event in a real-world context. Cross-sectional studies using retrospective reports cannot reveal the temporal dynamics ( Markowitz, 2022 ). Longitudinal studies often assess a few time points in a limited period, constraining researchers’ ability to map the precise trajectories of psychological responses in the weeks and months following a traumatic event.…”
Section: Psychological Adjustment and Language Usementioning
confidence: 99%